Declarative agent languages and technologies VIII 8th International Workshop, DALT 2010, Toronto, Canada, May 10, 2010, Revised, Selected and Invited Papers - Omicini, Andrea; Sardina, Sebastian; Vasconcelos, Wamberto (Lecture notes in computer science, 2011)
This book constitutes the thoroughly refereed post-workshop proceedings of the 8th International Workshop on Declarative Agent Languages and Technologies, DALT 2010, held in Toronto, Canada, on May 10, 2010, as a satellite workshop of the 9th International Joint Conference on Autonomous Agents and Multiagent Systems, AAMAS 2010. The 7 revised full papers presented together with 4 invited lectures were carefully selected during two rounds of reviewing and improvement from 24 initial submissions. DALT aims to make formal methods and declarative technologies and approaches available to and understood by a broader segment of the multi-agent research community; the papers are organized in topical sections on BDI rational agents, communication, coordination and negotiation, as well as social aspects and control systems.